Improving Arabic Vocabulary among Form 2 Students at Temerloh Distric, Pahang using the 'Snap Card' Game - Hussain, Yasmin; Muhamad Romli, Taj Rijal (SIBAWAYH Arabic Language and Education, 2024)
This study aims to investigate the effectiveness of the Snap Card intervention in enhancing the mastery of Arabic vocabulary among secondary school students. Specifically, the research focuses on form 2 students, located in Temerloh, Pahang. The total population consisted of 42 students, while the sample comprised 22 students, selected through a simple random sampling technique. The study utilized both quantitative and qualitative research methods, employing pre-test and post-test assessments as well as semi-structured interviews to evaluate the impact of the intervention. The findings indicate that the Snap Card intervention significantly improved the students' ability to recall and master Arabic vocabulary, as evidenced by the comparison of pre-test and post-test scores. In addition to enhanced vocabulary retention, the study also observed a marked increase in students' motivation to learn Arabic, suggesting that the intervention positively influenced students' attitudes toward language learning. The qualitative data obtained from interviews further supported these findings, indicating a greater enthusiasm for and engagement in Arabic language lessons among participants. The study concludes that the Snap Card intervention is an effective and efficient tool for improving the acquisition of Arabic vocabulary and motivating students in the learning process. This intervention presents a promising approach to addressing common challenges faced in language acquisition, particularly in enhancing vocabulary retention and learner motivation. The results underscore the potential of interactive and engaging methodologies in facilitating language learning, thereby contributing to the broader body of research on effective language pedagogy.